The one by whom scandal comes - Girard, René (Studies in violence, mimesis, and culture series, 2014)
"Why is there so much violence in our midst?" Ren ̌Girard asks. "No question is more debated today. And none produces more disappointing answers." In Girard's mimetic theory it is the imitation of someone else's desire that gives rise to conflict whenever the desired object cannot be shared. This mimetic rivalry, Girard argues, is responsible for the frequency and escalating intensity of human conflict. For Girard, human conflict comes not from the loss of reciprocity between humans but from the transition, imperceptible at first but then ever more rapid, from good to bad reciprocity. In this landmark text, Girard continues his study of violence in light of geopolitical competition, focusing on the roots and outcomes of violence across societies latent in the process of globalization. The volume concludes in a wide-ranging interview with the Sicilian cultural theorist Maria Stella Barberi, where Girard's twenty-first century emphases on the continuity of all religions, global conflict, and the necessity of apocalyptic thinking emerge